Euroscepticism and Protestant Heritage: The Role of Religion on EU Issue Voting. Issue 1 (March 2020) - Scherer, Margarete
Abstract: This paper focuses on the historical ties between Protestantism and the nation-state, as well as between Catholicism and supranationalism, to widen the political science debate on different conditions of EU issue voting . Research suggests that the political context in each nation-state shapes the extent to which individual Eurosceptic attitudes influence the decision to vote for Eurosceptic parties. In addition to this, I expect that a nations' religious background responds differently to this relationship. Using data from the 2014 European Parliament elections, I show that citizens from predominantly Protestant countries actually decide for Eurosceptic parties if they hold negative attitudes towards European integration. In contrast, citizens from predominantly Catholic countries may or may not vote for Eurosceptic parties, but their voting decision is not based on individual EU attitudes such as support for European integration, trust in EU institutions or European identity.